Changes in countermovement vertical jump performance metrics during a professional men's basketball game - Cabarkapa, D.; Philipp, N.; Eserhaut, D.; Fry, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: While multifaceted in physical performance parameters influencing success, basketball is a sport that is largely dictated by an athlete`s ability to efficiently use their stretch-shortening cycle. One of the non-invasive testing modalities used to quantify this neuromuscular phenomenon, as well as identify fatigue and athletes` readiness status, is the countermovement vertical jump (CVJ) performed on a force plate. Thus, the purpose of this study was to examine how some of the most commonly studied CVJ performance metrics respond to on-court competitive demands.